Peran Media Digital Dalam Meningkatkan Partisipasi Generasi Muda Pada Pengajian Akbar Ahad Wage - Siti Nur Aisah; Agussalim; Agus Mukmin; Purwandari, Elce; Depi Putri (AL-MUTSLA, 2025)
This study aims to explore the role of digital media, particularly Facebook and WhatsApp, in increasing youth participation in the Pengajian Akbar Ahad Wage (Sunday Grand Islamic Gathering) in Sukakarya District. Employing a qualitative approach, data were collected through in-depth interviews with religious leaders, youth organization leaders (IPNU–IPPNU), active and less active youth participants, and community members. The findings reveal that digital media plays a strategic role in disseminating information, fostering engagement, and creating a religious space that aligns with the digital habits of younger generations. Key supporting factors include easy access to technology, the active involvement of youth in digital promotion, and support from parents and community leaders. However, challenges such as low digital literacy, unstable internet infrastructure, and lack of content innovation remain. In conclusion, digital media has the potential to become an inspirational and transformative tool for religious outreach if managed collaboratively and contextually.